Physical, chemical and microbiological properties of a Dystrophic Yellow Latosol using manipueira Características físicas, químicas e microbiológicas de um Latossolo Amarelo distrófico com uso de manipueira - João J. da Silva Júnior; Eugênio F. Coelho; José A. do V. Sant'Ana; Adriana M. de A. Accioly (Engenharia Agrícola, 2012)
The study aimed to evaluate chemical, microbiological and hydro-physical changes of a Dystrophic Yellow Latosol, receiver of different levels of manipueira (cassava wastewater) application, in the cultivation of 'Terra Maranhão' banana. The experimental design was a randomized block with three replications in a factorial scheme 3 x 4, in which it was considered three soil depths and four levels of manipueira. It was evaluated the weighted mean diameter of the aggregate, the percentage of aggregation at different periods, soil density, particle density, porosity and soil saturated hydraulic conductivity, in addition to pH of P (mg dm -3), K (mg dm-3), Ca (cmolc dm-3), Mg (cmolc dm-3), Ca+Mg (cmolc dm-3), Al (cmolc dm-3), Na (cmolc dm -3), H+Al (cmolc dm-3), CEC (cmolc dm-3), V%, OM (g kg-1), soil microbial biomass (Ug Cg-1 dry soil), acid phosphatase (Ug PNP g-1 h-1). The use of manipueira influenced some physical characteristic of the soil, but it was not possible to specify the effect of increasing application dosage. Therefore, the application did not affect the biological indicators assessed in the soil or its pH. The use of manipueira as a fertilizer in the doses used in this study showed low increase of K, P, H+Al and Al in the soil and a good increase of Mg, Ca and Ca+Mg, Na, CEC and V%. O trabalho teve por objetivo avaliar as variações das características químicas, microbiológicas e físico-hídricas de um Latossolo Amarelo distrófico receptor de diferentes doses de aplicação de manipueira, em cultivo de banana 'Terra Maranhão'. O delineamento experimental foi em blocos casualizados, com três repetições, em esquema fatorial 3 x 4, no qual se consideraram três profundidades do solo e quatro doses de manipueira. Foram avaliados o diâmetro médio ponderado do agregado, a percentagem de agregação em diferentes períodos, a densidade do solo, a densidade da partícula, a porosidade e a condutividade hidráulica saturada do solo, além do pH, P (mg dm-3), K (mg dm-3), Ca (cmolc dm-3), Mg (cmolc dm-3), Ca+Mg (cmolc dm-3), Al (cmolc dm-3), Na (cmolc dm-3), H+Al (cmolc dm-3), CTC (cmolc dm-3), V%, MO (g kg-1), biomassa microbiana do solo ( Ug C.g-1 solo seco) de Fosfatase ácida (Ug PNP g-1.h-1). O uso da manipueira influenciou algumas caracteristicas físicas do solo, mas não foi possível precisar o efeito do aumento da dosagem de aplicação. Entretanto, a aplicação não afetou os indicadores biológicos avaliados no solo nem o pH do solo. A utilização de manipueira como fertilizante, nas doses utilizadas no presente trabalho, apresentou baixo incremento de K, P, H+Al e Al no solo e um bom incremento de Mg, Ca e Ca+Mg, Na , CEC e V%.